Enhanced Ferroelectric Polarization in Au@BaTiO3 Yolk‐in‐Shell Nanostructure for Synergistic Boosting Visible‐Light‐ Piezocatalytic CO2 Reduction - Jun Hu; Rufang Zhao; Jingren Ni; Wei Luo; Hongjian Yu; Hongwei Huang; Boyuan Wu; Yang Wang; Jie Han; Rong Guo (Advanced Science)
Abstract Developing efficient photo‐piezocatalytic systems to achieve the conversion of renewable energy to chemical energy emerges enormous potential. However, poor catalytic efficiency remains a significant obstacle to future practical applications. Herein, a series of unique Au@BaTiO3 (Au@BT) yolk‐shell nanostructure photo‐piezocatalyst is constructed with single Au nanoparticle (Au NP) embedded in different positions within ferroelectric BaTiO3 hollow nanosphere (BT‐HNS). This special structure showcases excellent mechanical force sensitivity and provides ample plasmon‐induced interfacial charge‐transfer pathways. In addition, the powerful piezoelectric polarization electric field induced by the enhanced ferroelectric polarization electric field via corona poling treatment in BT‐HNS further promotes charge separation, CO2 adsorption and key intermediate conversion. Notably, BT with single Au NP encapsulated into hollow nanosphere shell with reinforced polarization (Au@BT‐1‐P) shows synergistically improved photo‐piezocatalytic CO2 reduction activity for producing CO with a high production rate of 31.29 µmol g−1 h−1 under visible light irradiation and ultrasonic vibration. This work highlights a generic tactic for optimized design of high‐performance and multifunctional nanostructured photo‐piezocatalyst. Meanwhile, these yolk‐in‐shell nanostructures with single Au nanoparticle as an ideal model may hold great promise to inspire in‐depth exploration of carrier dynamics and mechanistic understanding of the catalytic reaction.